ZFONE SECURITY ANALYSIS OF VIDEO CALL SERVICE USING GENERAL NEWORK DESIGN PROCESS METHOD(GNDP) - Priyatna, Bayu; Lia Hananto, April; Istambul, Rozahi (International Journal of Psychosocial Rehabilitation, 2020)
VoIP (Voice over Internet Protocol) is one of the services implemented in wireless local area networks. However, VoIP that uses wireless technology as a media data stream Video Call service has a high risk of being tapped by sniffing attacks [2]. To avoid this from happening, you can add a security system to the service, one of which is to use Zfone security. Adding a security system will affect the work of the Video Call service on the quality of service. The author uses the General Network Design Process (GNDP) study method. After testing security by cropping images, Zfone affects the security of video calls on WLAN by turning conversations between client images black. Although Zfone managed to secure from eavesdropping on video calls, Zfone also had an impact on the deterioration of the quality of the Video Call service.